Learning by Association? Interorganizational Networks and Adaptation to Environmental Change - Kraatz, Matthew S. (Academy of Management Journal, 1998)
A study of 230 private colleges over 16 turbulent years supports two arguments: (1) Strong ties to other organizations mitigate uncertainty and promote adaptation by increasing communication and information sharing. (2) Networks can promote social learning of adaptive responses, rather than other, less productive, forms of interorganizational imitation. Colleges that were members of smaller, older, and more homogeneous intercollegiate consortia were more likely to undertake fundamental curriculum changes. Colleges tended to imitate similar consortium partners that were performing well rather than larger and more prestigious partners. Implications for organizational adaptation and the growing network perspective within organization theory are considered.